Implementasi Kebijakan Pemenuhan Kebutuhan Sumber Daya Manusia di Lingkungan Direktorat Jenderal Perhubungan Laut Kantor Pusat Kementerian Perhubungan Jakarta - Juwita , Citra Dara; Firzah , Muhammad (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
The background of this thesis discusses the Implementation of Fulfillment of Human Resource Needs in the Directorate General of Sea Transportation, Head Office of the Ministry of Transportation, Jakarta. The purpose of this study is to analyze and evaluate the Implementation of Fulfillment of Human Resource Needs in the Directorate General of Sea Transportation, to analyze and evaluate what factors are obstacles in improving the Implementation of Fulfillment of Human Resource Needs in the Directorate General of Sea Transportation, to analyze and evaluate efforts to overcome obstacles in the Implementation of Fulfillment of Human Resource Needs in the Directorate General of Sea Transportation. The research method used is qualitative. Qualitative research methods are often called naturalistic research methods because the research is conducted in natural conditions, also known as ethnographic methods. Qualitative research is conducted on natural objects that develop as they are, are not manipulated by researchers and the presence of researchers does not greatly affect the dynamics of the object. The focus of this research is very important in a qualitative research. The focus of the research is intended to provide a qualitative study, while limiting the research in order to choose which data is relevant and which data is not relevant. The results of the study indicate that the Implementation of Fulfillment of Human Resource Needs in the Directorate General of Sea Transportation has shown positive results but there is still room for further improvement, especially in terms of communication